2006
DOI: 10.1097/01.aog.0000237100.29870.cc
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A for Chronic Pain and Pelvic Floor Spasm in Women

Abstract: Australian Clinical Trials Registry, http://www.actr.org.au/, ACTRN012605000515695 LEVEL OF EVIDENCE: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
194
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 27 publications
2
194
0
4
Order By: Relevance
“…A previous systematic review pointed this out, indicating that controlled trials of treatments for vaginismus are needed [9,11]. Nevertheless, results observed in this meta-analysis are in agreement with at least 3 other studies that have also found results indicating the effectiveness of botulinum toxin to treat other disorders associated with the pelvic floor musculature such as postoperative dyspareunia [23], pelvic floor spasm [24], and vulvodynia [25]. Furthermore, Pacik [11] has reported ‘success rates in excess of 90%’ in an unpublished sample of 81 patients.…”
Section: Discussionsupporting
confidence: 85%
“…A previous systematic review pointed this out, indicating that controlled trials of treatments for vaginismus are needed [9,11]. Nevertheless, results observed in this meta-analysis are in agreement with at least 3 other studies that have also found results indicating the effectiveness of botulinum toxin to treat other disorders associated with the pelvic floor musculature such as postoperative dyspareunia [23], pelvic floor spasm [24], and vulvodynia [25]. Furthermore, Pacik [11] has reported ‘success rates in excess of 90%’ in an unpublished sample of 81 patients.…”
Section: Discussionsupporting
confidence: 85%
“…It was found that local BTX-A injections efficiently decrease pain in patients suffering from bladder pain syndrome/ interstitial cystitis, prostatitis and pelvic-floor muscle disorder (Abbott et al, 2006., Chung et al, 2012, El-Khawand et al, 2013, Gottsch et al, 2011, Kuo, 2013, Pinto et al, 2013, Smith et al, 2004, Zermann et al, 2000. In addition, there are isolated case reports on the beneficial effect of BTX-A on non-cardiac chest pain (Maradey-Romero and Fass, 2014) and perineal pain (Lim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Abbott et al [18] reported their double-blind, randomized, placebo-controlled trial of botulinum neurotoxin injection in patients with chronic pelvic pain of more than 2 years' duration and evidence of pelvic floor muscle spasm. Patients received 80 U of onabotulinumtoxinA (n= 30) or saline injection (n=30) into the pubococcygeus and puborectalis muscles.…”
Section: Pelvic Pain Syndromesmentioning
confidence: 99%